ASPEK HUKUM DAN ANALISIS PENGELOLAAN DAN PARTISIPASI PEREMPUAN DALAM PENGURANGAN MARINE DEBRIS PADA KAWASAN WISATA PESISIR PANTAI PALLIPIS POLEWALI MANDAR - eka dewi kartika; salma laitupa; asrullah asrullah (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2023)
This research analyzes the legal aspects of marine debris management in Kab. Polewali Mandar, especially in the Pallipis Beach tourist area. Management of marine debris or marine debris needs to be implemented as a form of responsibility for the regional government which has the authority to fulfill the Main Performance Indicators for Marine Debris management through a program to clean up marine debris and develop coastal aquaculture, which is a structured program which is a national movement from the center to the regions. The form of participation of women living in the Pallipis coastal tourism area in reducing marine debris is by having marine debris management skills by categorizing marine debris, first mega debris with the 2R (reuse and repair) management method and marine debris with the category micro debris with the 4R management method (reuse, repair, refill, recycle).